Indonesian Legal Efforts to Prevent Statelessness in Children Resulting from Unregistered Mixed Marriages - Pramesti, Indira Yekti Widya; Fahrozi, Muhmmad Helmi (Dinasti Research, 2025)
Indonesia's legal efforts to prevent statelessness in children born to unregistered mixed marriages between Indonesian citizens (WNI) and foreign nationals (WNA) are an important concern because the unclear status of the marriage causes children to lose the administrative basis for obtaining citizenship. The research method used is normative juridical with a legislative and case approach, one of which is the case of Efa Maulidiyah in Malaysia. The results of the study show that children of Indonesian mothers still have civil relations based on Article 43 paragraph (1) of Law Number 1 of 1974 and Constitutional Court Decision Number 46/PUU-VIII/2010, so they are entitled to Indonesian citizenship based on the principle of ius sanguinis in accordance with Article 4 letter (d) of Law Number 12 of 2006. To overcome administrative obstacles, the Indonesian government implemented Permenkumham Number 6 of 2025 as a mechanism for confirming the citizenship status of children born to mixed marriages and strengthening legal protection for Indonesian children abroad.